Proces ryzyka i prawdopodobieństwo ruiny dla ubezpieczeń wieloopcyjnych - Homa, Magdalena (Risk process and ruin probability in multi-state insurance, 2006)
In the literature there are described the methods of analyzing and pricing in traditional life insurance. But in practice the traditional life insurance respects only the basic insurance products, which in reality are more complicated. This reason determined that in my article I consider a multi-state insurance policies, which are more attractive and better adopted to needs of clients. All activity of the insurer are connected with the risk. Risk in multi-state insurance can be investigate in two aspects: protection and financial risk (connected with calculation of premium, calculation of mathematical reserves or analysis of risk process). The essence of my work is the discussion on the form of risk process and probability of ruin in multi state insurance. I presented the form of the risk process and methods of estimation of ruin probability. Knowledge of risk process permits to describe and estimate the “riskness” of the insurance portfolio. Ruin probability determines essential measure of financial activity of the insurer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 119-129